2018
DOI: 10.3390/en11051272
|View full text |Cite
|
Sign up to set email alerts
|

A PESTLE Policy Mapping and Stakeholder Analysis of Indonesia’s Fossil Fuel Energy Industry

Abstract: Indonesia has a long-standing history of reliance on fossil fuels, which reflects the country's vast reserves of crude oil, natural gas, coal, and other resources. Consequently, the potential of Indonesia's fossil energy industry is both complex and multi-layered. This paper aims to carry out a policy mapping and stakeholder analysis of Indonesia's fossil energy industry, adopting a PESTLE (Political, Economic, Social, Technology, Legal, and Environmental) approach, which allows identification of multidiscipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Within the context of our research, PESTLE is a valuable tool to determine driving forces of M&As in the energy industry, because it is a strong analytical tool and may be used for understanding the external environment and landscape of various projects, businesses, and industries. Framework of PESTLE analysis is frequently used by business and management practitioners to investigate the environment in which they operate or plan to launch new operations [17]. Furthermore, PESTLE analysis may be used to monitor the macroeconomic or other external factors that have an impact on that environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of our research, PESTLE is a valuable tool to determine driving forces of M&As in the energy industry, because it is a strong analytical tool and may be used for understanding the external environment and landscape of various projects, businesses, and industries. Framework of PESTLE analysis is frequently used by business and management practitioners to investigate the environment in which they operate or plan to launch new operations [17]. Furthermore, PESTLE analysis may be used to monitor the macroeconomic or other external factors that have an impact on that environment.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the PESTLE framework may be used to provoke further research directions [18]. PESTLE framework has been employed by various scholars in the field [13,[17][18][19]. In the context of this paper, the PESTLE analysis focuses on various changes in the industry that researchers, practitioners, scholars, and policymakers should address in order to approach M&As in the energy industry and adopt solutions that would benefit related stakeholders.…”
Section: Methodsmentioning
confidence: 99%
“…There are a number of pre-existing computer ethics case studies, for example, those provided by the ACM (https://ethics.acm.org/integrity-project/case-studies/), but it was felt that the lessons would be more effective if case studies were identified that would be both relevant to the students and of interest to them. To help brainstorm some of the relevant content, a PESTLE (Political, Economic, Sociological, Technological, Legal and Environmental) analysis was undertaken [37], yielding four key areas that were deemed to be relevant and appealing to the students: Social (the 2020 Irish state examinations), Political (the 2016 political bias of Google), Technical (autonomous cars), and Legal (judicial sentencing software), each of which will be detailed in section 3 of this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Further, within the last decade, some researchers have used the actor‐centred approach in which the actor is the main unit of analysis. In particular, exploring actors' behaviour towards energy policies (Dzikrurrokhim, 2021; Enzary, 2017; Yudha & Tjahjono, 2019), identifying actors' interests (Jakob et al, 2020; Yudha et al, 2018) and preferences (Yudha et al, 2021), and explaining the institutional barriers (Marquardt, 2017; Yudha & Tjahjono, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%